A universal model for predicting the effective shear modulus of two-dimensional porous materials. (July 2017) - Guo, Zaoyang; Wang, Lei; Chen, Yang; Zheng, Lingli; Yang, Zhenjun; Dong, Leiting
Abstract: A new method is proposed to predict the effective shear modulus of two-dimensional (2D) porous materials with large porosities, which is called the Large Porosity Model (LPM). The LPM can be used as a complement for the classic Three Phase Model (TPM), which is only valid when the porosity is relatively small. Through bridging the LPM and the classic TPM, a Universal Porosity Model (UPM) is developed. In order to assess the performance of the UPM, a series of representative volume elements (RVEs) of porous materials are constructed, with different volume ratios, shapes, and numbers of voids. By comparing the UPM predictions to the finite element simulation results, it is demonstrated that the UPM gives accurate predictions (relative error always less than 10%) of the shear modulus among the entire range of porosities (from 0% to 100%), for different Poisson ratios of the matrix materials. Highlights: A Large Porosity Model (LPM) is proposed to predict the effective shear modulus of two-dimensional (2D) porous materials with large porosities. Through bridging the LPM and the classic Three Phase Model (TPM), a Universal Porosity Model (UPM) is developed. UPM gives accurate predictions (relative error always less than 10%) of the shear modulus among the entire range of porosities (from 0% to 100%), for different Poisson ratios of the matrix materials.